2021
DOI: 10.3389/fpsyg.2021.647196
|View full text |Cite
|
Sign up to set email alerts
|

Feelings Related to the COVID-19 Pandemic Among Patients Treated in the Oncology Clinics (Poland)

Abstract: Background: The number of cancer patients is constantly growing. Both WHO and IARC report that this number may reach up to 24 million new diagnosed cases in the next two decades. The proposed treatment and especially the diagnosis can have a significant impact on an individual's approach to the disease, as well as on the patient's quality of life.Objectives: The study aimed to assess the quality of life, feelings, and fear of cancer-treating oncological patients, before and during the COVID-19 pandemic.Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Engagement in these types of activities may have prevented more substantial declines in overall activity compared with other studies of adults during the COVID-19 pandemic [ 49 ]. While there are fewer reports of declines in HRQOL that have been systematically observed during COVID-19, Grajek et al recently reported declines of 2% among 450 patients actively treated for cancer [ 50 ]. Therefore, the high satisfaction with the gardening intervention may have mitigated steeper reductions in HRQOL that may have been noted otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement in these types of activities may have prevented more substantial declines in overall activity compared with other studies of adults during the COVID-19 pandemic [ 49 ]. While there are fewer reports of declines in HRQOL that have been systematically observed during COVID-19, Grajek et al recently reported declines of 2% among 450 patients actively treated for cancer [ 50 ]. Therefore, the high satisfaction with the gardening intervention may have mitigated steeper reductions in HRQOL that may have been noted otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…The online screening was completed by a total of 103 health professionals. PTSD symptoms were measured by the authors using the PCL-5, while depression symptoms were measured using the PHQ-9 questionnaire [ 64 , 65 ]. After analyzing the results of the online survey, the authors contacted participants who scored above the cut-off for the PCL-5 or PHQ-9.…”
Section: The Mental Condition Of Health Personnel and The Covid-19 Pa...mentioning
confidence: 99%
“…At the same time, social quarantine and difficult access to medical services may result in the deterioration of mental and physical health (including weight gain) [ 1 ]. Given the escalation in many cases, humankind is facing countless psychological problems, from those related to taking precautions and maintaining safety to those caused by separation [ 2 ]. From the somatic point of view, the biggest problem associated with isolation was the lack of possibility of direct contact with medical professionals, and thus the aggravation of many chronic (coexisting) diseases.…”
Section: Introductionmentioning
confidence: 99%